Multiparametric optical and MR imaging demonstrate inhibition of tumor angiogenesis natural history by mural cell therapy. Issue 3 (7th October 2013) - Faye, Nathalie; Clément, Olivier; Balvay, Daniel; Fitoussi, Victor; Pidial, Laetitia; Sandoval, Federico; Autret, Gwennhael; Silvestre, Jean Sébastien; Dean, Carole Leré; Alison, Marianne; Fournier, Laure S.
<x xml:space="preserve">Abstract</x> Purpose To determine whether functional imaging using MRI and fibered confocal fluorescence microscopy (FCFM) could be used to monitor cell therapy by mural progenitor cells (MPC). Methods Fifty mice bearing TC1 murine xenograft tumors were allocated into: control (n = 17), sham (phosphate buffer saline, n = 16), and MPC‐treated (MPC, n = 17) groups. MRI was performed before (D0) and 7 days (D7) after injection measuring tumor size, R2* under air, oxygen, and carbogen using blood oxygen level dependent (BOLD) and f (fraction linked to microcirculation), D* (perfusion related coefficient) and Dr (restricted diffusion coefficient) using diffusion‐weighted sequences based on the IVIM (intravoxel incoherent motion) method. FCFM was performed at D7 measuring "index leakage" (capillary permeability). Results Tumor growth was significantly slowed down in the MPC‐treated animals (P = 0.002) on D7. R2*air significantly decreased in controls between D0 and D7 (P = 0.03), reflecting a decrease in tumor oxygenation. ΔR2*O2CO2 significantly increased in controls between D0 and D7 (P = 0.01) reflecting loss of vessel response to carbogen. D* significantly decreased in controls between D0 and D7 (P = 0.03). Finally, "index leakage" was lower in the MPC‐treated tumors (P = 0, 009). Conclusion Treatment by MPC resulted in slowing down of tumor growth, capillary permeability decrease, and stabilization of tumor angiogenesis. Magn Reson Med 72:841–849, 2014. © 2013 Wiley Periodicals, Inc.